The first report of a Chinese family with McLeod syndrome. (3rd June 2014) - Man, Bik Ling; Yuen, Yuet Ping; Fu, Yat Pang
Abstract : We report the first case of a Chinese family with McLeod syndrome (MLS). The two affected brothers show significant phenotypic heterogeneity. The index case has peripheral acanthocytosis, choreoathetosis of his feet, a slowly progressive neuropathy and myopathy, and an elevated serum creatine kinase (CK) level. His elder brother has more prominent chorea of the shoulders, epilepsy, a rapidly progressive neuropathy and normal serum CK. The diagnosis of MLS was confirmed by a genetic test which showed a hemizygous frameshift mutation in the XK gene.